Motif Penggunaan Aplikasi LYSN Di Kalangan Fandom NCTzen Indonesia - Sarah Amarissa Girsang; Duddy Zein; Yuliani Dewi Risanti (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The Korean Wave is a rising phenomenon in Indonesia. South Korean entertainment companies capitalize on this by introducing an innovation called LYSN, an application designed to enhance the quality of relationships between fans and idols. This research aims to explore the motives behind the usage of the LYSN app among NCTzen fandom. The research employs a qualitative approach, utilizing in-depth interviews as the data collection technique with informants meeting specific criteria. The findings reveal four motives for using LYSN: surveillance, diversion, personal relationships, and personal identity.